After the Digital Tornado Networks, Algorithms, Humanity - Werbach, Kevin (Social Sciences, 2020)
Once a seemingly unambiguous benefit to society, the internet is now the basis for invasions of privacy, massive concentrations of power, and manipulation. Featuring leading technology scholars, this collection examines the challenges of building networks and algorithms that benefit humanity. This title is also available as Open Access on Cambridge Core.